(untitled) (Research, Society and Development, 2025)
The study aimed to assess patient satisfaction with Telenfermagem. It is an observational, descriptive, cross-sectional study of a quantitative nature. A total of 178 patients who used telenfermagerm between July 2023 and December 2024 were interviewed. Most calls (61.8%) were made by women, 91.6% of participants reported being satisfied, 5.6% were neutral, and 3.9% were dissatisfied with the service; 21.2% reported some type of problem, such as delays in service. As advantages, 49.4% mentioned avoiding travel and 43.2% mentioned faster access to information; as disadvantages, 3.9% mentioned communication difficulties, 3.4% mentioned the lack of human contact, and 2.2% mentioned delays in service.It can be concluded that patient satisfaction levels are high and that the program is undergoing improvements and can contribute to more humane care, with greater availability for individualized follow-up of cancer patients.